2015
DOI: 10.3109/0886022x.2014.1001281
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin E-coated dialysis membranes on anemia, nutrition and dyslipidemia status in hemodialysis patients: a meta-analysis

Abstract: Background: This was controversial whether vitamin E-coated dialyzer therapy was beneficial for the complications associated with hemodialysis. Therefore, we performed this systematic review to evaluate the effects of vitamin E-coated dialyzer. Methods: Related trials were searched from multiple electronic databases. We conducted meta-analysis to assess changes in the predefined outcomes using RevMan 5.3 software. Results: Meta-analysis showed vitamin E-coated dialyzer therapy could decrease erythropoietin (EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
(101 reference statements)
3
15
0
1
Order By: Relevance
“…The absence of effect on such parameters was in agreement with previous analyses focusing on fewer studies [7] .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The absence of effect on such parameters was in agreement with previous analyses focusing on fewer studies [7] .…”
Section: Discussionsupporting
confidence: 82%
“…Finally, in line with previous meta-analyses [7] , our results confirmed that the use of ViE-m did not influence other parameters of interest for dialysis patients, such as dialysis adequacy, lipid profile, intradialytic blood pres- sure, dialysis adequacy, serum albumin, uric acid and WBC count. Our review has some points of strength and also a few limitations that deserve to be mentioned.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Other interventions for improving hyporesponsiveness to ESA treatment have been proposed. A systematic review suggested that a vitamin E‐coated dialyzer may reduce ESA resistance . Recently, we examined if statin prescriptions would improve ESA hyporesponsiveness using the Japan DOPPS cohort, and suggested that statins may slightly reduce ESA hyporesponsiveness in patients undergoing HD …”
Section: Esa Hyporesponsiveness In Patients Undergoing Hdmentioning
confidence: 99%